PEMANFAATAN LAHAN BEKAS TAMBANG SEBAGAI MEDIA TUMBUH TANAMAN BUDIDAYA DENGAN APLIKASI DOLOMIT DAN SERESAH TANAMAN DENGAN TANAMAN UJI KAILAN - Nurul Puspita Palupi (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2012)
The post mining soil has generally known for its high acid, poisonous compound and low macro nutrient concentration. (N, P, K, Ca, and Mg).  At this particular soil condition, many of the cultivation plants cannot grow well.  Therefore, a research needs to be conducted in order to repair the post mining soil condition by means of increasing the pH and macro nutrient concentration through calcification and litter addition.   This research had been done in November until December 2012 at the Agronomy Laboratory, Agriculture Faculty of The Mulawarman University used the Complete Random Design of Factorial (RAL) 2 x 5, with 3 times repetition.  The first factor was the Dolomite (D) with 2 levels (d0 = 0 g dolomite/kg soil, and d1 = 6,06 g dolomite/kg soil.  The second factor was the litter (T) with 5 levels (t0 = 0 g/kg soil, t1 = acacia litter (Acacia Mangium Will) 100 g/kg soil, t2 = Arachis pintoi litter Krapov. & W.C. Greg 100 g/kg soil, t3= seashore flower (Wedelia trilobata (L.) Hitchc) litter 100 g/kg soil and T4 = sengon litter (Albizzia Falcataria) 100 g/kg soil.  This research used the Kailan plant (Brassica oleraceae L. var acephala DC).   On the soil which had no dolomite, litter treatment A. Pintoi Krapov.&.K.C.Greg and sengon had positive impact on the pH increase, also for C-organic, N-total, and decreased the C/N value ratio, and Al3+content, followed by the seashore flower litter also influenced positively to the pH, C-organic, N-total increase, and decreased Al3+content.  Acacia influenced positively to the C-organic and N-total also, but negatively influenced the C/N ratio and Fe solubility.  The dolomite treatment with sengon litter gave additional height to the plants, leaves quantity and wide better than other treatment.